Estrategias didácticas para el desarrollo de la expresión oral de los estudiantes de octavo año del colegio Leonardo Da Vinci, Riobamba. - Saigua León, Adrián Marcelo (2022)
The objective of this research was to analyze the didactic strategies that develop the oral expression of eighth-grade students of the Leonardo Da Vinci Educational Unit in Riobamba, province of Chimborazo, knowing that didactic strategies are procedures and methods techniques, and activities that benefit learning. At the same time, oral expression is considered the communicative ability that encompasses the mastery of lexical and grammatical pronunciation. The methodology used is a mixed approach, of field type, descriptive, essential, bibliographic-documentary, with a non-experimental design, the population was 22 eighth year students, the sample was non-probabilistic and intentional, as a technique the survey was used and the instrument was a questionnaire through which it was possible to generate statistical tables and graphs that allowed us to perform an analysis, The conclusion reached was that teachers use different didactic strategies, one of them being individual activities such as oratory, declamation, book reading, expositions, which favor the development of oral expression, these types of activities allow students to lose their fear of expressing themselves or speaking in public; This generated the importance of designing didactic strategies through activities that benefit the development of oral expression; finally, it is recommended to apply to students the proposed intervention plan to lose the fear of speaking in public, with these strategies the student will be able to communicate effectively during the teaching-learning process, with respect to the teachers of the area of Language and Literature, to train them in methodologies to improve the oral expression of their students.